Nematic DNA Thermotropic Liquid Crystals with Photoresponsive Mechanical Properties. Issue 34 (11th July 2017) - Zhang, Lei; Maity, Sourav; Liu, Kai; Liu, Qing; Göstl, Robert; Portale, Giuseppe; Roos, Wouter H.; Herrmann, Andreas
Abstract : Over the last decades, water‐based lyotropic liquid crystals of nucleic acids have been extensively investigated because of their important role in biology. Alongside, solvent‐free thermotropic liquid crystals (TLCs) from DNA are gaining great interest, owing to their relevance to DNA‐inspired optoelectronic applications. Up to now, however, only the smectic phase of DNA TLCs has been reported. The development of new mesophases including nematic, hexagonal, and cubic structures for DNA TLCs remains a significant challenge, which thus limits their technological applications considerably. In this work, a new type of DNA TLC that is formed by electrostatic complexation of anionic oligonucleotides and cationic surfactants containing an azobenzene (AZO) moiety is demonstrated. DNA–AZO complexes form a stable nematic mesophase over a temperature range from −7 to 110 °C and retain double‐stranded DNA structure at ambient temperature. Photoisomerization of the AZO moieties from the E‐ to the Z‐ form alters the stiffness of the DNA–AZO hybrid materials opening a pathway toward the development of DNA TLCs as stimuli‐responsive biomaterials. Abstract : Nematic DNA thermotropic liquid crystals are prepared by electrostatic complexation of anionic oligonucleotides and cationic surfactants containing an azobenzene (AZO) moiety. Upon irradiation with UV‐light, the E‐ to Z‐ isomerization of AZO proceeds smoothly in the DNA–AZO liquid crystals and grants access to photocontrol over their mechanical performance.